Business Plan Niche Tourism Pada Tour & Travel Pelesiran Holiday di Saat Pandemi Covid-19 - Faisal Nuralamsyah (JURNAL PARIWISATA VOKASI, 2022)
The Covid-19 pandemic has a considerable impact on the tourism sector, one of which is to travel business owners. Holiday melting as one of the tourist travel businesses is quite affected by the state of the Covid-19 pandemic, because it has been dependent on mass tourism activities and bus rentals. Therefore, in order to keep the business afloat, in making a special interest tour package (niche tourism) one of them as an alternative tour package during the pandemic. In this paper contains planning in creating a new business package so that the business can remain afloat. Using descriptive qualitative methods coupled with the existence of literature studies. So it can describe the actual condition at the time of this study. The results of this study are attributed segmenting targeting and positioning from Pelesiran Holiday targeting male and female consumers with vulnerable age 2-55 years with a variety of educational backgrounds and jobs that have an interest in historical travel. The BEP obtained is 11 customer packages with payback period of 3 months 8 days.